2016
DOI: 10.1177/2229411220160107
|View full text |Cite
|
Sign up to set email alerts
|

Caries prevalence and oral hygiene status among 7-12 years old school children from rural and urban areas of Gautam Budh Nagar, U.P

Abstract: Dental caries is a common dental public health problem significantly found in both developed and developing countries. It is a dental disease which affects all ages but is particularly found in children. The study aimed to assess the caries prevalence and oral hygiene status in 7-12 years old school children of rural and urban areas of Gautam Budh Nagar, Uttar Pradesh India. Materials and Methods: A cross-sectional survey was carried out in school children who aged 7-12 years from rural and urban areas of Gaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
2
2
1
1
Order By: Relevance
“…The results of this study also showed that the mean OHI-S scores of students was approximately similar to OHI-S scores reported of students in India and other studies in Iran[3640] and better than the OHI-S scores reported of students in Nigeria, Thailand, Vietnam, Peru and some cities in India[25, 4145] and worse than Greece and Portugal[46–48]. Studies indicate that various variables, including conducting preventive programs, educating oral hygiene behaviors, changing attitude of families and dentists towards oral health in a positive manner, the provision of affordable, as well as acceptable and high-quality oral healthcare services all can affect gingival and periodontal health[16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results of this study also showed that the mean OHI-S scores of students was approximately similar to OHI-S scores reported of students in India and other studies in Iran[3640] and better than the OHI-S scores reported of students in Nigeria, Thailand, Vietnam, Peru and some cities in India[25, 4145] and worse than Greece and Portugal[46–48]. Studies indicate that various variables, including conducting preventive programs, educating oral hygiene behaviors, changing attitude of families and dentists towards oral health in a positive manner, the provision of affordable, as well as acceptable and high-quality oral healthcare services all can affect gingival and periodontal health[16].…”
Section: Discussionsupporting
confidence: 88%
“…The oral hygiene status among suburban students can be attributed to poor oral hygiene, not brushing or flossing and brushing or flossing infrequently. Limited access to professional dental care, restorative dentistry or any kind of dental treatment also influence oral health status [13, 15, 36, 73]. In this study, the odds ratio of calculus in urban schoolchildren was 5.21 times higher than that of suburban schoolchildren, which is different from the results of other studies[53, 6971].…”
Section: Discussioncontrasting
confidence: 84%
“…In our study, there was no correlation between DMFT and genders (p = 0.897), which is consistent with the studies by Dukic et al and Shabani et al, with no relationship between DMFT and genders was found (20,21). However, in the studies of Sharma et al and Seth et al in India and Oliveira et al in Brazil, the DMFT index was higher in girls (24,25,26), which could be due to the difference in the earlier eruption of permanent teeth in girls, which causes girls' teeth to be more exposed to decay (27).…”
Section: Discussionmentioning
confidence: 87%
“…Similar results were obtained in a study done by Seth et al among Indian children and Yazdani et al on Iranian children where girls seem to have better oral hygiene practices when compared to boys. 17,18 On contrary, study done by Ganesh et al among Chennai children and Zhu et al in China where there was no difference in toothbrushing behaviour according to gender. 19,20 The mean OHI-S score for those who used finger for cleaning their teeth was higher than those who used tooth brush for cleaning.…”
Section: Discussionmentioning
confidence: 94%